Rheological and structural characterization of gels from albumin and low methoxyl amidated pectin mixtures - Chaux-Gutiérrez, Ana María [UNESP]; Pérez-Monterroza, Ezequiel José [UNESP]; Mauro, Maria Aparecida [UNESP] (Elsevier, 2019)
The rheological behavior of gels prepared from albumin (ALB) and a mixture of ALB and low methoxyl amidated pectin (PEC) with different proportions were studied using oscillatory rheological tests, Fourier transform infrared spectroscopy (FT-IR spectroscopy), zeta potential measurements and confocal microscopy. The mixture was always 5% of the total solute. Assays were performed in two series, one in which all mixtures were adjusted to pH = 8 and another one without pH adjustment. The zeta potential values indicated the presence of a negative net charge on ALB-PEC gels. The rheological tests indicated a frequency dependence of the storage (G′) and loss (G”) moduli, with G’ > G’’. The presence of 1% and 2% of pectin in the mixture caused an increase in G’. However, a PEC concentration above 2% led to a decrease in G′ regardless of the pH or frequency. FT-IR spectroscopy indicated that as the PEC content increased, a higher proportion of β-sheet structures was found. Confocal microscopy also confirmed aggregation of ALB particles due to the PEC concentration.
Keywords: Biopolymers; Confocal microscopy; Gelation; Polysaccharides; Protein; Rheology